Integrasi Prinsip Riba Fadl dalam Kebijakan Uang Elektronik Syariah: Kajian Makroekonomi Islam atas Fatwa DSN-MUI No. 116/2017 - Ganda Yulida Trisakti Pamungkas (Tim Jurnal STAI KH. Zainuddin Ponpes Mojosari, 2026)
The advancement of digital technology has driven the transformation of payment systems toward the increasingly widespread use of electronic money in Indonesia, which, from the perspective of Islamic macroeconomics, is not only related to transaction efficiency but also encompasses aspects of monetary stability, wealth distribution, and economic justice. This study aims to analyze the integration of the principle of riba fadl within sharia-compliant electronic money policies based on the DSN-MUI Fatwa No. 116/DSN-MUI/IX/2017, as well as its implications from an Islamic macroeconomic perspective. The method employed is a qualitative descriptive-analytical approach using a literature review, drawing on sources such as academic journals, books, fatwas, and publications from relevant authoritative institutions. The findings indicate that the principle of riba fadl, which emphasizes value equivalence and spot transactions, serves as a fundamental basis for assessing the validity of electronic money mechanisms, particularly in the top-up process categorized as a ṣarf contract. Although the fatwa provides a normative foundation, its implementation still faces challenges related to service fees, digital business models, and the management of float funds, which may potentially lead to value imbalances. From the perspective of Islamic macroeconomics, the integration of this principle plays a significant role in maintaining financial system stability, promoting equitable distribution, and ensuring linkage with the real sector; therefore, strengthening regulation and supervision is necessary to ensure that sharia-compliant payment systems can develop in a stable, inclusive, and equitable manner.